2008
DOI: 10.1016/j.prevetmed.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the prevalence and associated risk factors for capped hock and the associations with bursitis in weaner, grower and finisher pigs from 93 commercial farms in England

Abstract: and in factors associated with locomotion (slipping and slip marks). These results indicate that the aetiology of capped hock and bursitis might differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 6 publications
1
13
0
4
Order By: Relevance
“…Among the set of monitored pigs, the majority was fattened on fully or partially slatted floors. A negative effect of slatted floors on the welfare Jorgensen (2003) and KilBride et al (2008). In our study, this effect has also been demonstrated by higher mortality of pigs transported after fattening to the slaughter house from slatted floor housing compared to pigs transported from solid floor housing.…”
Section: Discussionsupporting
confidence: 73%
“…Among the set of monitored pigs, the majority was fattened on fully or partially slatted floors. A negative effect of slatted floors on the welfare Jorgensen (2003) and KilBride et al (2008). In our study, this effect has also been demonstrated by higher mortality of pigs transported after fattening to the slaughter house from slatted floor housing compared to pigs transported from solid floor housing.…”
Section: Discussionsupporting
confidence: 73%
“…Lying on hard surfaces causes swellings and wounds on the limbs of the sows (Mouttotou et al, 1998;Rushen et al, 2007;Gillman et al, 2008;KilBride et al, 2008;von Wachenfeit et al, 2008). The fact that sows housed on rubber slat mats were at reduced risk of scores greater than the median for swellings on the limbs during both parities reflects the cushioning properties of the rubber floor.…”
Section: Discussionmentioning
confidence: 99%
“…The exceptions were calluses and capped hock where, because of the high prevalence of calluses and the very mild nature of capped hock score one [14], diseased sows were classified as those with a lesion score of two or three.…”
Section: Methodsmentioning
confidence: 99%